Vitamin D Levels and Lipid Response to Atorvastatin - José Luis Pérez-Castrillón; Laura Abad Manteca; Gemma Vega; Javier del Pino Montes; Daniel de Luis; Antonio Dueňas Laita (International Journal of Endocrinology)
Adequate vitamin D levels are necessary for good vascular health. 1,25-dihydroxycholecalciferol activates CYP3A4, an enzyme of the cytochrome P450 system, which metabolizes atorvastatin to its main metabolites. The objective of this study was to evaluate the response of cholesterol and triglycerides to atorvastatin according to vitamin D levels. Sixty-three patients with acute myocardial infarction treated with low and high doses of atorvastatin were included. Levels of total cholesterol, triglycerides, HDL cholesterol, and LDL cholesterol were measured at baseline and at 12 months of follow-up. Baseline levels of 25-hydroxyvitamin D (25-OHD) were classified as deficient (<30 nmol/L), insufficient (30–50 nmol/L), and normal (>50 nmol/L). In patients with 25-OHD <30 nmol/L, there were no significant changes in levels of total cholesterol (173±47 mg/dL versus 164±51 mg/dL), triglycerides (151±49 mg/dL versus 177±94 mg/dL), and LDL cholesterol (111±48 mg/dL versus 92 45± mg/dL); whereas patients with insufficient (30–50 nmol/L) and normal vitamin D (>50 nmol/L) had a good response to atorvastatin. We suggest that vitamin D concentrations >30 nmol/L may be required for atorvastatin to reduce lipid levels in patients with acute myocardial infarction.